PENGARUH BRAND AWARENESS, KUALITAS PRODUK, DAN WORD OF MOUTH (WOM) TERHADAP MINAT BELI SKIN CARE LOKAL DI SOCIOLLA STORE SURABAYA - Isriyatul Fadillah; M. Anang Firmansyah; Samsul Hadi; Muhammad Alhakim Danurwindo (PROCEEDING UMSURABAYA, 2022)
This study will examine the effect of Brand Awareness, Product Quality, and Word of Mouth (Wom) on Purchase Interest. The sampling technique in this study uses a simple random sampling technique because the sampling from population members is carried out randomly without regard to the existing strata in the population. The Technical data analysis used is the multiple linear regression analysis techniques. The data quality test used is a test of validity and reliability. The results of this study indicate that based on the F test, it is known that Fhitung > Ftable (11.450 > 2.72) and the value of Sig < 0.05 (0.000 < 0.05), which means at a significant level of 5%, Brand Awareness (X1) variable, Quality Product (X2), and Word of Mouth (WOM) (X3) simultaneously have a significant effect on the variable of Purchase Interest (Y) of local Skincare at Sociolla Store Surabaya.Keywords: Brand Awareness; product quality; and Purchase